Longitudinal Associations Between Household Solid Fuel Use and Handgrip Strength in Middle-Aged and Older Chinese Individuals: The China Health and Retirement Longitudinal Study - Liu, Yashu; Chang, Qing; Xia, Yang; Zhao, Yuhong (Frontiers in Public Health, 2022)
Background: Household solid fuels have been associated with changes of handgrip strength (HGS). However, no study has explored the longitudinal associations between household solid fuel use and HGS. Thus, the aim of our cohort study was to investigate the longitudinal associations between household fuel use and HGS. Methods: The study was based on the China Health and Retirement Longitudinal Study. A handheld dynamometer was used to measure HGS. Household fuel use statuses were collected using questionnaires. Analyses of covariance were performed to examine the associations between household fuel use and HGS. Results: The study included 9,382 participants during a four-year follow-up. The participants who used solid fuels for cooking had more decreases of HGS than those who used clean fuels (P < 0.0001). The least square means (95% CIs) of changes of HGS for participants who used solid fuels and those who used clean fuels for cooking were -1.67 (-2.15, -1.19) and -2.27 (-2.75, -1.79), respectively. The association between fuels used for heating and HGS was non-significant (P = 0.63). The interaction terms of sex to cooking fuels (P = 0.04) and smoking to cooking fuels (P < 0.001) were significant; men and participants who had ever smoked had higher decreases in HGS. Conclusion: Using household solid fuels for cooking but not heating was associated with more decreases in HGS. Proper ventilation and clean fuels should be promoted for public health.